2015
DOI: 10.1111/evj.12428
|View full text |Cite
|
Sign up to set email alerts
|

Validation ofIgGcut‐off values and their association with survival in neonatal foals

Abstract: Serum IgG values of <8 g/l in hospitalised foals were proportionally associated with mortality. We recommend immediate assessment of IgG concentrations in hospitalised foals and those with FTPI should receive prompt immunotherapy. The summary is available in Chinese - see Supporting information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 15 publications
2
32
2
4
Order By: Relevance
“…Equine neonates therefore rely on passive transfer of IgG via colostrum intake for humoral immunity to reduce the risk of infectious diseases in the first weeks of life (Jeffcott 1974b, McGuire et al 1977, Robinson et al 1993, Raidal 1996, Holznagel et al 2003, Thein et al 2005, Liepman et al 2015. Adequate serum IgG concentrations in foals are generally defined as ≥ 8 g/L (Koterba et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Equine neonates therefore rely on passive transfer of IgG via colostrum intake for humoral immunity to reduce the risk of infectious diseases in the first weeks of life (Jeffcott 1974b, McGuire et al 1977, Robinson et al 1993, Raidal 1996, Holznagel et al 2003, Thein et al 2005, Liepman et al 2015. Adequate serum IgG concentrations in foals are generally defined as ≥ 8 g/L (Koterba et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Failure of transfer of passive immunity (FTPI) is common in neonatal foals and predisposes them to severe infections . Early detection of http://FTPI is therefore important to ensure adequate and timely treatment .…”
mentioning
confidence: 99%
“…Early detection of http://FTPI is therefore important to ensure adequate and timely treatment . Immunoglobulin G (IgG) concentrations of >800 mg/dL measured 12–48 hour postnatum are generally considered adequate, and http://FTPI is commonly defined as partial http://FTPI at IgG concentrations of 400–800 mg/dL or total http://FTPI at IgG concentrations <400 mg/dL …”
mentioning
confidence: 99%
“…Immunoglobulin G concentration <400 mg/dL was the only variable with no statistical significance associated with nonsurvival in the multivariate analysis. A previous study investigated the relationship between IgG concentrations and nonsurvival and found an increased risk of mortality for foals with concentrations of <400 mg/dL and 400‐800 mg/dL compared to concentrations >800 mg/dL. It is possible that applying a cutoff of <800 mg/dL to predict nonsurvival in our study may have correlated better with mortality.…”
Section: Discussionmentioning
confidence: 99%